NF-κB-Induced Upregulation of miR-146a-5p Promoted Hippocampal Neuronal Oxidative Stress and Pyroptosis via TIGAR in a Model of Alzheimer’s Disease - Lei, Bo; Liu, Jiaxin; Yao, Zhihui; Xiao, Yan; Zhang, Xiaoling; Zhang, Yueting; Xu, Jianguo (Frontiers in Cellular Neuroscience, 2021)
Alzheimer’s disease (AD) is a common neurodegenerative disorder that places a heavy burden on patients and society. Hippocampal neuronal loss is a hallmark of AD progression. Therefore, understanding the mechanism underlying hippocampal neuronal death would be of great importance for the diagnosis and treatment of AD. This study aimed to explore the molecular mechanism via which nuclear factor kappa β (NF-κB) promotes hippocampal neuronal oxidative stress and pyroptosis in AD. We collected serum samples from 101 healthy elderly people and 112 patients with AD at the Affiliated Hospital of Kunming University of Science and Technology between January 2017 and January 2020. Commercially available human hippocampal neurons (HHNs) were used to establish an AD model (AD-HHN) following Aβ25–35 treatment. The mRNA expression levels of NF-κB and pyroptosis markers [NLR family pyrin domain-containing 3, caspase-1, interleukin (IL)-1β, and interleukin-18] mRNA and the expression level of miR-146a-5p in the serum samples of patients with AD and AD-HHNs were determined by quantitative reverse transcription polymerase chain reaction. Oxidative stress indices (reactive oxygen species, malondialdehyde, nicotinamide adenine dinucleotide phosphate, superoxide dismutase, glutathione, and catalase) were measured by Enzyme-Linked Immunosorbent Assay (ELISA). The expression of proteins [NF-κB, TP53-induced glycolysis and apoptosis regulator (TIGAR), and pyroptosis markers] was tested by western blotting. The relationship between miR-146a-5p and TIGAR was investigated using a dual luciferase reporter gene assay. We found that NF-κB and miR-146a-5p were highly expressed, while TIGAR was low expressed in patients with AD and AD-HHNs. In addition, there was a significant positive correlation between the expression levels of NF-κB and miR-146a-5p, but a negative correlation between NF-κB mRNA and TIGAR mRNA in patients with AD, as well as miR-146a-5p and TIGAR mRNA in patients with AD. In AD-HNNs, miR-146a-5p targeted and downregulated the expression of TIGAR. Knockdown of NF-κB or overexpression of TIGAR markedly attenuated oxidative stress and pyroptosis in AD-HHNs, while concurrent overexpression of miR-146a-5p inhibited these effects. In conclusion, NF-κB-induced upregulation of miR-146a-5p promoted oxidative stress and pyroptosis in AD-HNNs by targeting TIGAR.